How Audit Factors and Information Technology Affect Audit Report Lag: The Moderating Role of Firm Size? - mardjono, enny susilowati; Kurniawati, Rahma; suhartono, entot; purwantoro, purwantoro (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2026)
This study examines the influence of audit factors and information technology implementation on audit report lag, with firm size as a moderating variable, in energy sector companies listed on the Indonesia Stock Exchange from 2020–2024. Using a quantitative descriptive approach with secondary data, 100 companies were selected through purposive sampling. Data were analyzed using descriptive statistics, classical assumption tests, and moderated regression in SPSS 25. Results show that only Audit Opinion significantly increases audit report lag. Auditor Switching, Audit Tenure, and Information Technology show no significant effect, and firm size does not moderate any of these relationships.